Application of 3D Hepatic Plate-Like Liver Model for Statin-Induced Hepatotoxicity Evaluation - Xu, Jiecheng; Pan, Daogang; Liao, Wei; Jia, Zhidong; Pan, Mingxin; Weng, Jun; Han, Xu; Li, Shao; Li, Yang; Liang, Kangyan; Zhou, Shuqin; Peng, Qing; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Drug-induced liver injury (DILI) is one of the main reasons of withdrawals of drugs in postmarketing stages. However, an experimental model(s) which can accurately recapitulates liver functions and reflects the level of drug hepatotoxicity is lack. In this study, we assessed drug hepatotoxicity using a novel three-dimensional hepatic plate-like hydrogel fiber (3D-P) co-culture system. Methods: During the 28-day culture period, the liver-specific functions, hepatocyte polarity, sensitivity of drug-induced toxicity of 3D-P co-culture system were evaluated with 2D co-culture, collagen sandwich co-culture, and 3D hybrid hydrogel fiber co-culture as controls. High-content imaging and analysis (HCA) methods were used to explore the hepatotoxicity mechanism of five statins. Results: The 3D-P co-culture system showed enhancing liver-specific functions, cytochrome P450 enzymes (CYPs) metabolic activity and bile excretion, which were considered to result from improved hepatocyte polarity. Three of the statins may cause acute or chronic hepatotoxicity by via different mechanisms, such as cholestatic liver injury. Conclusion: Our 3D-P co-culture system is characterized by its biomimetic hepatic plate-like structure, long-term stable liver specificity, and prominent bile secretion function, making it applicable for acute/chronic drug hepatotoxicity assessments.